Talking about cancer with confidence: evaluation of cancer awareness training for community-based health workers. (September 2014) - Grimmett, Chloe; Macherianakis, Alexis; Rendell, Helen; George, Helen; Kaplan, Gwen; Kilgour, Gillian; Power, Emily
Aims: To examine the impact of cancer awareness training for community-based health workers on confidence to talk about cancer, and knowledge of cancer risk factors and signs and symptoms. Methods: Community-based health workers from Sandwell, Birmingham and Solihull were invited to take part in one of 14 one-day training workshops. Trainees completed questionnaires at the beginning of the workshop and were followed up one month later. Confidence in talking about cancer was examined. Knowledge of cancer risk factors and signs and symptoms was assessed. Trainees were asked to rate the usefulness of the workshop, whether they would recommend it to others and whether they had put what they had learnt into practice. Results: A total of 187 community-based health workers took part in the workshops, and 167 (89%) completed the one-month follow-up. Considerable improvements were observed in confidence to discuss cancer. For example, the proportion of participants reporting feeling 'very confident'/'fairly confident' in discussing signs and symptoms of cancer increased from 32% to 96% ( p < .001). Substantial improvements in trainees' knowledge were also observed, with 79% of participants correctly identifying 10 out of 11 known risk factors for cancer at one month compared with 21% before training ( p < .001). Average (unprompted) recall of cancer signs and symptoms also increased from 2.3 (±1.6) to 2.7 (±1.5), ( p = .02). Most trainees (83%) rated the workshop as 'very useful', and 89% said they would 'definitely' recommend the workshop. Conclusion: The cancer awareness training was reviewed positively by community-based health workers and led to improvements in confidence to talk about cancer, and knowledge of risk factors and warning signs of cancer. It is hoped that raising awareness among this group will help them to communicate and drive behaviour change in the at-risk populations with whom they work.